Atomization in the Acoustic Field of a Hartmann Whistle. (March 2013) - Narayanan, S.; Srinivasan, K.; Sundararajan, T.
The current work experimentally investigates the effect of Hartmann cavity acoustics on the atomization of droplet sprays. Initially, the experiments are conducted on a single droplet to understand its behavior in the sound field of a Hartmann whistle. The atomization studies on single droplet reveal that the existence of sound field causes the droplet to undergo large deformation and become irregular in shape. The degree of droplet deformation is quantified based on smaller circularity and larger Feret's diameter. The increase in cone angle of spray to a higher value in the presence of acoustics in comparison to its absence shows that the acoustics enhances the atomization. The stroboscopic visualization of sprays in the presence of acoustics further reveals the breakup of ligaments, large scatter as well as the formation of more number of droplets, indicating atomization enhancement.